Leading Green, Acting Green: Green HRM as a Bridge from Leadership to Employees’ Sustainable Practices in Sasirangan SMEs - MEISKE CLAUDIA; Bachri, Ahmad Alim; Dahniar; Dewi, Maya Sari; Wandari, Wimby; Wahyudi, Muhammad Haikal; Sya'ban, Rahmat (FEB - Universitas Lampung, 2025)
This study examines the influence of Green Transformational Leadership (GTL) on Employee Green Behavior (EGB) with Green Human Resource Management (Green HRM) as a mediating variable in small and medium-sized enterprises (SMEs) producing Sasirangan fabric in Banjarmasin, Indonesia. Using a quantitative approach, data were collected through a census survey of 155 employees across 41 SMEs. The data were analyzed with Structural Equation Modeling using Partial Least Squares (SEM-PLS). The results show that GTL significantly affects both EGB and Green HRM, while Green HRM positively influences EGB. Furthermore, Green HRM mediates the relationship between GTL and EGB, with the indirect effect stronger than the direct effect. These findings highlight the critical role of leadership and human resource practices in fostering pro-environmental behavior among employees in traditional creative industries. The study contributes to extending sustainability research beyond large corporations by offering empirical evidence from SMEs rooted in local cultural heritage. Keywords: Green Transformational Leadership, Employee Green Behavior, Green Human Resource Management, Sustainability, SMEs, Sasirangan Industry